COMPLEX RECONSTRUCTION OF MNLZ-3 OF BELORUSSIAN METALLURGICAL WORKS, DIRECTED AT IMPROVEMENT OF BLOOMS QUALITY, WIDENING OF ASSORTMENT AND PRODUCTIVITY BOOSTING - A. A. Sotnikov; A. V. Demin; S. V. Terletskij (Литьë и металлургия)
It is shown that carried out complex of reconstruction enterprises at MNLZ-3 enabled to improve its efficiency by 26% at providing of required level of qualitative characteristics, as well as to master a new type of product – continuously-cast round slug in diameter 200mm for production of seamless tubes in tube-rolling shop.